Mikheil Saakashvili’s Lobbying Activities in USA - Kevkhishvili, Mariana (Politics / პოლიტიკა, 2023)
The former president of Georgia, Mikheil Saakashvili, will turn to American lobbyists for help from 2022. He was arrested on October 1, 2021 upon his arrival in Georgia and remains in custody to this day. It was during this period that he began to hire lobbyists in the United States of America to make the international political community aware of his detention as a political prisoner and for his release on humanitarian grounds. The paper analyzes the lobbying activities of Mikheil Saakashvili in the USA in 2022-2023. On the basis of qualitative research methods, in particular, through the analysis of secondary sources, scientific articles have been studied and the documents uploaded on Fara, signed between Mikheil Saakashvili and lobbying companies, have been analyzed. A total of three lobbying companies worked for Mikheil Saakashvili in America. As of today, the contract with all three companies has been terminated. Despite numerous attempts by lobbyists to put pressure on the Georgian authorities and court proceedings in Georgia by Western politicians, American high-ranking officials, media and other non-governmental persons, Mikheil Saakashvili remains in prison.
Keywords: Mikheil Saakashvili, Lobby, USA, Georgia